A Methods engineering study on Moonbake, Inc. - Landoy, Abigail (College of Engineering, 2005)
Moonbake is currently operating for 24 hours with 2 shifts (each shift having twelve working hours) to sustain the market's demand on chocolate crinkles. This resulted from some problems on their operation proper. Based on the data gathered by the group through frequent plant visits and on the time study they conducted, the standard time for each of the processes was calculated. They were able to reduce the working time from 24 hours to 16 hours with two shifts (each shift having eight working hours) by utilizing all the batter mixers available in the plant, by adding one more encrusting machine and by hiring seven more workers for each shift, which lead to lesser salaries expense. The savings in the salaries expense can pay off the cost of the additional encrusting machine in three years time. The group also observed some minor problems on the operation proper, which lead to production inefficiency. These include the area for cooling that is not specified, idleness of some machines and working conditions that cause too much fatigue to workers- all constitute a sort of delay. All of these are tackled on the following pages and their corresponding suggested solutions. The accomplishment of the group's recommendations highly guarantees that the company will come up with an improved system-a more efficient production in terms of quantity and quality. The improvements that are suggested do not only account for the management's advantage but also for the workers' who are really behind the production.